FDX1 expression predicts favourable prognosis in clear cell renal cell carcinoma identified by bioinformatics and tissue microarray analysis - Huang, Xing; Wang, Tao; Ye, Jiali; Feng, Huayi; Zhang, Xiangyi; Ma, Xin; Wang, Baojun; Huang, Yan; Zhang, Xu (Frontiers in Genetics, 2022)
Ferredoxin 1 (FDX1), an iron-sulfur protein, is responsible for electron transfer in a range of metabolic redox reactions. Clear cell renal cell carcinoma (ccRCC) is an aggressive cancer characterised by metabolic reprogramming, and FDX1 a critical regulator of cuproptosis. Nonetheless, the expression profile and prognostic value of FDX1 associated with clinicopathological features in ccRCC remain largely unelucidated. In this study, we integrated a series of public bioinformatic mining to explore FDX1 mRNA and protein profiles across human cancers and cell lines and validated its expression and prognostic value, especially in ccRCC. We found that FDX1 mRNA and protein expression were aberrantly downregulated and associated with the grade, stage, and nodal metastasis of ccRCC, whereas in adjacent non-tumour kidney tissue, it was abundantly expressed and cytoplasmically localised in renal tubular epithelial cells. Multivariate analysis showed that low FDX1 expression contributed to unfavourable overall and disease-free survival. Functional enrichment of FDX1 co-expressed genes in ccRCC mainly involved mitochondrial dysfunction in various metabolic processes and biological oxidation, in addition to iron-sulfur cluster biogenesis. Furthermore, FDX1 modulates immunological infiltration to affect prognosis. Thus, FDX1 downregulation is mechanistically attributable to ccRCC tumourigenesis and is a promising prognostic biomarker to stratify patients with ccRCC.